The selection of a mode of urban transportation: integrating psychological variables to discrete choice models (2011)
A study using revealed preference surveys and psychological testswas conducted. Key psychological variables of behavior involved in the choice of transportation mode in a population sample of the Metropolitan Area of the Valle de Aburrá were detected. The experiment used the random utility theory for discrete choice models and reasoned action in order to assess beliefs. This was used as a tool for analysis of the psychological variables using the sixteen personality factor questionnaire (16PF test). In addition to the revealed preference surveys,two other surveys were carried out: onewith socio-economic characteristics and the other with latent indicators. This methodology allows for an integration of discrete choice models and latent variables. The integration makes the model operational and quantifies the unobservable psychological variables. The most relevant result obtained was that anxiety affects the choice of urban transportation mode and showsthat physiological alterations, as well as problems in perception and beliefs, can affect the decision- making process.